2021
DOI: 10.1080/08965803.2021.1886541
|View full text |Cite
|
Sign up to set email alerts
|

“Don't Know What You Got till It’s Gone”: The Community Reinvestment Act in a Changing Financial Landscape

Abstract: This study provides new evidence on the impact of the Community Reinvestment Act (CRA) on mortgage lending by taking advantage of an exogenous policy shock in 2014, which caused significant changes in neighborhoods' CRA eligibility in the Philadelphia market. The loss of CRA coverage leads to an over 10 percent decrease in purchase originations by CRA-regulated lenders. While nondepository institutions replace approximately half, but not all, of the decreased lending, their increased market share was accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2 Some research has found positive impacts of the CRA on lending (e.g., Butcher and Muñoz 2017;Ringo 2022;Lee and Bostic 2020;Ding and Nakamura 2021) and related outcomes (e.g., Avery et al 2003;Agarwal et al 2012), whereas other studies have argued that the CRA has been largely ineffective in (e.g., Bhutta 2011;Hylton 2006;White 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Some research has found positive impacts of the CRA on lending (e.g., Butcher and Muñoz 2017;Ringo 2022;Lee and Bostic 2020;Ding and Nakamura 2021) and related outcomes (e.g., Avery et al 2003;Agarwal et al 2012), whereas other studies have argued that the CRA has been largely ineffective in (e.g., Bhutta 2011;Hylton 2006;White 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several contemporary papers also explore possible substitution effects of the CRA. Ding and Nakamura (2021) examines the Philadelphia area and finds a negative origination effect of a loss in CRA eligibility; specifically, the authors find that an eligibility loss causes CRAcovered institutions to decrease originations and FHA loan originations to increase by a smaller amount. Brevoort (2022) uses a recent subsample of the same Home Mortgage Disclosure Act data we use to show that banks increase loan purchases in CRA-eligible areas, substituting away from Government Sponsored Entity (GSE) purchases while leaving originations the same.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper also contributes to the more specialized literature examining the CRA's impact. Most research studies the CRA's effects on residential mortgages (Bostic and Robinson 2003, Dahl, Evanoff, and Spivey 2010, Bhutta 2011, Avery and Brevoort 2015, Ding and Nakamura 2020, Begley and Purnanandam 2021) finding mixed results regarding the effectiveness of the CRA on expanding mortgage lending. Fewer studies analyze the CRA's effects on lending to small firms.…”
mentioning
confidence: 99%
“…Ours is not the first study of the CRA to exploit the income threshold, using RD to estimate the impact across tracts(Avery, Calem and Canner, 2003;Bhutta, 2011;Avery and Brevoort, 2015;Bostic and Lee, 2017;Lee and Bostic, 2020), and some have used difference-in-differences based on changes in CRA eligibility resulting from MSA boundary changes(Ding and Nakamura, 2021;Ringo, 2017;Ding, Lee and Bostic, 2020), although none of these use firm-level data or examine racial inequality. Our identification of the CRA effect exploits a much large number of changes associated with the redefinition of CRA eligibility nationwide, as described further below.…”
mentioning
confidence: 99%